The Influence of the Reward and Recognition System on Employee Motivation at the Regional Development Bank Sidoarjo Branch - Okky Kusuma Putri Adhyaksa*; Nanik Kustiningsih; Sri Rahayu (Riwayat: Educational Journal of History and Humanities, 2024)
This research examines the influence of reward and recognition systems on Employee Motivation at the Regional Development Bank Sidoarjo Branch. Sample in this study were 80 employees of Bank Jatim Sidoarjo. Analytical tools used is multiple linear regression. The research results show that each variable, the Reward and Recognition System is related and has a positive effect on employee motivation at Bank Jatim Sidoarjo employees. Keywords: Reward System; Recognition; Employee Motivation.